Guild Constitution - Kabale University (Kabale University, 2022)
The Kabale University Guild Constitution has an indispensable part to play in the political, social growth and development of the University. Student political activism in higher Institutions of learning is real and needs direction and support by the University council, Senate, Management, Staff and the student community itself. The council is ready and willing to give due guidance to the Student Guild by continually supporting them whenever necessary. What makes the Guild Constitution unique and relevant is the fact that the students, Management and the University Council have actively contributed to the making of this constitution until its final approval. It also clearly reflects the Mission of the University: “To excel in generation and dissemination of relevant knowledge and skills development for lifelong learning and community service.”